PERAN DAN POTENSI MUSUH ALAMI DALAM PENGENDALIAN HeUcoverpa armigera (HUBNER) PADA KAPAS - NURINDAH NURINDAH; DWI ADI SUNARTO; SUJAK SUJAK (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
The role and potency of natural enemies in controlling HeUcoverpa armigera Hubner in cottonHeUcoverpa armigera. known as the cotton bollworm, is one of cotton productivity limiting factors. Efforts in controlling this pesl have been directed lo (he use of its natural enemies, viz. parasiloids. predator and insect pathogens in conservation techniques The study was conducted in two activities. The irst activity was the inventory of parasiloids and predators of// armigera. which was conducted from 1986 to 1999 in the cotton development area in Central Java (Rembang, Pati, and Grobogan). East Java (Situbondo, Banyuwangi, Tuban. and Lanongan), NIB (Menangabaris. Lokopriya, and Sandubaya), and NTF (Maumere, Wailiti. and Larantuka). The second activity was to sludy the potency of dominant parasiloids and predators in cotton, which was conducted in 1999/2000 in the Research Instalaiion for Tobacco and Fibre Crops, Asembagus. The objectives of the study were to evaluate Ihe diversity of natural enemies, particularly parasiloids and predators, and their role in controlling Ihe population of // armigera in cotton. The inventory of parasiloids and predators was conducted to 15 and 21 species, respectively. The predominant parasiloids were Trichogramma-loidea armigera Nagaraja (egg parasitoid) and Eriborus argenteopilosus Camreon (larval parasitoid). The predominant predators were Deraeocoris indianus Carvalho, Campylomma diversicornis Rcuter (Hemiptera Miridae). Paederus fasciatus Curtis (Coleoptera Staphylinidac) and Coccinellid beetles (Coleoptera Coccincllidac). These predators feed on eggs and small larvae of //. armigera. The potency of these parasiloids and predator, as mortality factors of the pesl, was quantitatively studied in insecticide sprayed and unsprayed cotton ields. The egg and larval parasiloids caused mortality of //. armigera eggs and larvae as high as 65% and 21%, respectively. The predators suppressed // armigera population by 82%, so that its population was lower than that of the plots treated with insecticide. These suppressions resulted in a significantly lower damage of cotton fruiting bodies (4.3-8.0% on sprayed plots vs.1.7-3.4% on unsprayed plots) and hence, a signiicantly higher production of seed cotton ( I 838 kg/ha on sprayed plots vs. 2 170 kg/ha on unsprayed plots). Thereore, // armigera population on collon basically could be managed by its natural enemies below its action threshold, when Hie natural enemies were allowed to build up their population.